Construction of Fe‐doped NiS–NiS2 Heterostructured Microspheres Via Etching Prussian Blue Analogues for Efficient Water‐Urea Splitting. Issue 14 (18th February 2022) - Huang, Shoushuang; Zhang, Qian; Xin, Peijun; Zhang, Jie; Chen, Qiaochuan; Fu, Jie; Jin, Zhiqiang; Wang, Qing; Hu, Zhangjun
Abstract: Developing efficient and robust non‐precious‐metal‐based catalysts to accelerate electrocatalytic reaction kinetics is crucial for electrochemical water‐urea splitting. Herein, Fe‐doped NiS–NiS2 heterostructured microspheres, an electrocatalyst, are synthesized via etching Prussian blue analogues following a controlled annealing treatment. The resulting microspheres are constructed by mesoporous nanoplates, granting the virtues of large surface areas, high structural void porosity, and accessible inner surface. These advantages not only provide more redox reaction centers but also strengthen structural robustness and effectively facilitate the mass diffusion and charge transport. Density functional theory simulations validate that the Fe‐doping improves the conductivity of nickel sulfides, whereas the NiS–NiS2 heterojunctions induce interface charge rearrangement for optimizing the adsorption free energy of intermediates, resulting in a low overpotential and high electrocatalytic activity. Specifically, an ultralow overpotential of 270 mV at 50 mA cm −2 for the oxygen evolution reaction (OER) is achieved. After adding 0.33 M urea into 1 M KOH, Fe‐doped NiS–NiS2 obtains a strikingly reduced urea oxidation reaction potential of 1.36 V to reach 50 mA cm −2, around 140 mV less than OER. This work provides insights into the synergistic modulation of electrocatalytic activity of non‐noble catalysts for applications in energy conversion systems. Abstract : In the present work, an electrocatalyst of Fe‐doped NiS–NiS2 heterostructured microspheres is synthesized via etching Prussian blue analogues following a controlled annealing treatment. The Fe‐doping improves the conductivity of nickel sulfides, whereas the NiS–NiS2 heterojunctions induce interface charge rearrangement for optimizing the adsorption free energy of intermediates, thus resulting in a low overpotential and high electrocatalytic activity.